Resistance to the novel nitroimidazole drug class in Mycobacterium tuberculosis - Astrid Gail, Paulse (Stellenbosch : Stellenbosch University, 2023)
Astrid Gail, Paulse. 2023. Resistance to the novel nitroimidazole drug class in Mycobacterium tuberculosis. Unpublished master's dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/52eb99f9-0718-432e-85d9-9d723fa425f0